COVID-19 Outbreak During Inpatient Rehabilitation: Impact on Settings and Clinical Course of Neuromusculoskeletal Rehabilitation Patients. (12th March 2021) - Spielmanns, Marc; Pekacka-Egli, Anna-Maria; Cecon, Mikis; Witassek, Fabienne; Schoendorf, Sabine; Lutz, Dietmar; Hermann, Matthias
Abstract : Objective: The COVID-19 pandemic affects a large number of patients. The impact on feasibility and outcome of rehabilitation during COVID-19 actually remains unclear. Nosocomial infection of healthcare workers or hospitalized patients is common, and prevention of nosocomial infections during rehabilitation is challenging. Therefore, we analyzed a cohort of nosocomial infected COVID-19 patients in a single-center inpatient rehabilitation clinic and described performance and outcome. Design: The cohort ( N = 27) describes patients with nosocomial SARS-CoV-2 infection while participating in neuromusculoskeletal rehabilitation. Infection was caused by an initially unidentified so-called superspreader. We compared this cohort with all neuromusculoskeletal rehabilitation inpatients of 2019 (comparison group). Normally distributed continuous variables were presented as mean with standard deviation and the t test was used for comparison between groups. Linear regression was used to assess the impact of COVID-19 on Functional Independence Measure at discharge. Results: COVID-19 patients were mostly male (66.7%) with an age of 71.5 ± 12.3 yrs. Age, sex, and cumulated comorbidities of the comparison group ( n = 786) were not different from the COVID-19 group. A total of 92.6% of COVID-19 patients had a mild or moderate course, two patients had to be referred to acute hospital because of respiratory failure, and one of these patients died in the acute hospital. After implementation of a strict hygiene concept, no further nosocomial COVID-19 infections were detected. The rehabilitation duration was significantly longer in the COVID-19 group (54.2 ± 23.6 days vs. 32.1 ± 17.7 days, P < 0.001). Daily therapy duration was 132.3 ± 44 mins before SARS-CoV-2 infection and reduced to 81.9 ± 27.3 mins during COVID-19 ( P < 0.001). After discontinuation of isolation measures, therapy duration increased significantly (99.3 ± 70.2 mins, P < 0.05). The baseline Functional Independence Measure score was higher in the COVID-19 group (91.93 ± 25.64 points vs. 82.98 ± 22.73 points) and Functional Independence Measure improvements were lower in COVID-19 patients than in the 2019 comparison group (6.96 ± 8.96 points vs. 20.3 ± 15.98 points, P < 0.001). COVID-19 infection itself had a strong negative impact on Functional Independence Measure change as identified by regression analysis. Linear regression analysis showed that COVID-19 reduced the Functional Independence Measure at discharge by 8.9 points (95% CI = −14.725 to −3.097, P = 0.003) after correction for Functional Independence Measure at admission, age, sex, and morbidity index at admission. Conclusions: COVID-19 had a strong negative impact on rehabilitation benefits as assessed by Functional Independence Measure. Neuromusculoskeletal rehabilitation could be continued, but all patients received less therapy minutes during isolation. After implementation of a strict COVID-19–specific hygiene concept, no further infections were detected.